2017
DOI: 10.1093/eurheartj/ehx086
|View full text |Cite
|
Sign up to set email alerts
|

Improving public health by improving clinical trial guidelines and their application

Abstract: Evidence generated from randomized controlled trials forms the foundation of cardiovascular therapeutics and has led to the adoption of numerous drugs and devices that prolong survival and reduce morbidity, as well as the avoidance of interventions that have been shown to be ineffective or even unsafe. Many aspects of cardiovascular research have evolved considerably since the first randomized trials in cardiology were conducted. In order to be large enough to provide reliable evidence about effects on major o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Regulators can also advise on the level of information that needs to be collected. Clinical narratives are burdensome, may reduce trial participation, and should be focused only on those serious adverse events where such data may be informative, such as suspected unexpected serious adverse reactions 39 . Reliable review of safety during a trial is best achieved by examining randomized comparisons of aggregated data by the unblinded Data and Safety Monitoring Boards.…”
Section: Conference Structurementioning
confidence: 99%
“…Regulators can also advise on the level of information that needs to be collected. Clinical narratives are burdensome, may reduce trial participation, and should be focused only on those serious adverse events where such data may be informative, such as suspected unexpected serious adverse reactions 39 . Reliable review of safety during a trial is best achieved by examining randomized comparisons of aggregated data by the unblinded Data and Safety Monitoring Boards.…”
Section: Conference Structurementioning
confidence: 99%
“…However, central statistical monitoring of trialrelated data, in combination with targeted site monitoring informed by statistical analysis, can be a more effective and efficient method of detecting important errors during the conduct of a trial and identifying opportunities for improvement prospectively. 22 Initiatives for reducing complexity CTTI and ICH are working to make clinical trials more efficient and responsible for clarifying the processes used and the roles and responsibilities of the parties conducting the trials. While these initiatives hold tremendous potential for promoting efficiency in these key areas, poor alignment of incentives for all actors in the clinical trial ecosystem remains a significant obstacle.…”
Section: Operational Complexity and The Expense Of Clinical Trialsmentioning
confidence: 99%
“…Finally, large, simple trials that address questions of major public health importance have been advocated for decades as one of the pillars of evidence-based medicine [9]. All in all, more and larger investigator-led trials are needed, and it is crucially important to identify ways of conducting them as cost-effectively as possible [10,11]. In particular, excessive regulation of investigator-led trials, using industrysponsored trials as a model, is both unnecessary and counterproductive [11].…”
Section: Why Are Investigator-led Clinical Trials Needed?mentioning
confidence: 99%
“…All in all, more and larger investigator-led trials are needed, and it is crucially important to identify ways of conducting them as cost-effectively as possible [10,11]. In particular, excessive regulation of investigator-led trials, using industrysponsored trials as a model, is both unnecessary and counterproductive [11]. Taruno et al (2019) have shown that, in Japan, the enactment of the Clinical Trial Act in March 2018 has resulted in a halving of the number of interventional cancer trials registered in the UMIN and jRCT clinical trial registries ( Fig.…”
Section: Why Are Investigator-led Clinical Trials Needed?mentioning
confidence: 99%